Yersinia enterocolitica intestinal infection with ileum perforation: report of a clinical case - De Bernardis, B.; Torresini, G.; Bruschi, M. (Acta Biomedica Atenei Parmensis, 2004)
Yersinia enterocolitica infection is responsible in human beings for ileocolitis appearing with abdominal pain, diarrhoea and fever. This kind of disease usually heals spontaneously with no remarkable complication. Intestinal perforation is a rare complication of the disease. To date only eleven cases of surgical complications arising from abscess and intestinal perforation due to Yersinia enterocolitica have been reported in literature. In our clinical case the patient, who had previously undergone appendicectomy, required urgent surgery for pelvi-peritonitis due to intestinal perforation on necrotic-ulcerative ileitis with adenomesenteritis from Yersinia enterocolitica. The surgical treatment combined with intestinal resection and targeted antibiotic therapy have proved to be effective.